Effect of cutting position in the mother plant and use of auxin on the rooting efficiency of cuttings in four varieties of Cannabis sp. - Axel Voisin; Sebastián Gómez; Esteban Colmann Lerner; Oswaldo Aranda Mosquera; Blanca Villarreal; Sandra Sharry; Christian Weber (Agricultura)
The regulatory framework for the production, industrialization, and commercialization chain of Cannabis sp. plant, its seeds, and derived products for industrial and/or medicinal use has recently been approved in Argentina. This work addresses the importance of producing genetically stable plant material, especially in medicinal production where cloning plants with known characteristics is essential for large-scale production. The study analyzed the influence of cutting position on the mother plant and the use of rooting agent on the rooting ability of four varieties Cannabis sativa L. Significant differences were found between genotypes evaluated for their rooting ability, although no clear effect was determined from positioning cuttings on different parts mother plants. It is concluded that there is a varietal component to observed response that can change with or without addition rooting agent, mainly affecting root length and weight. These findings suggest that growers could select rooting techniques that maximize success across some variety cultivars while eliminating those difficult to root from their production systems.